Interactive Learning Media on Key Figures of Indonesian Independence Proclamation - Kusuma, Aniek Suryanti; Welda, Welda; Yudiarta, I Putu (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2025)
Education is a vital necessity in people's lives. One of the media that can be used is Interactive Learning Media, which can present material in visual form, as well as simulate material that is difficult to convey verbally. The author plans to provide material on Introduction to Key Figures Involved in the Proclamation of Independence, which is expected to facilitate students’ learning process. The research location is Jagapati Village, Abiansemal District, Badung Regency, Bali. The data collection methods used include interviews, observation, documentation, and literature review. The testing process involved both alpha and beta testing. The number of respondents was 32 people, consisting of 28 fifth-grade students, 2 subject matter experts in Social Studies for fifth grade at SD N 1 Jagapati, and 2 media experts. The results showed that the interactive learning media had a positive impact, with an evaluation score of 86% from teachers, indicating that the media is beneficial for teaching. The student evaluation score was 89.996%, showing a positive effect on student learning, while an evaluation score of 78% from university lecturers indicated that the media is suitable for use. It can therefore be concluded that Interactive Learning Media is highly practical for use by both students and teachers in the Social Studies learning process.